Testosterone undecanoate treatment for muscle weakness in a male with hypogonadotropic hypogonadism delayed puberty: A case report - Dicky Moch Rizal; Nandia Septiyorini (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Puberty is a series of physical development and sexual maturation that aims to achieved reproductive capacity. The hypothalamic-pituitary-gonadal (HPG) axis has an important role in the normal process of puberty. Disruption in the HPG axis causes hormonal disturbances, one of which is hypogonadotropic hypogonadism, which is associated with delayed puberty. Hormonal disorders can also cause various problems besides the reproductive system, such as muscle weakness, lack of energy, and an increased risk of bone fractures. We report the case of a male patient who complained of predominant muscle weakness, did not show signs and symptoms of puberty, and had an idiopathic hypogonadotropic hypogonadism who unresponsive to human chorionic gonadotropin (hCG) therapy. We decided to administered Testosterone Undecanoate (TU) therapy to overcome the problem of delayed puberty and complaints of muscle weakness experienced by the patient. TU therapy has shown beneficial effects in these patients by increasing testosterone levels, increasing penis length, and eliminating complaints of muscle weakness.